Concepções da história na Teologia da Libertação e conflitos de representação na Igreja Católica (1971-1989) - Pereira, Danillo Rangell Pinheiro (2013)
In this research we seek to study some main intellectual elaborations of Liberation Theology. From reading some of the works of two important theologians of this current, Clodovis Boff and Leonardo Boff, we reflect on the conceptions of history that are present in their writings published between the years from 1971 to 1989. Such theological formulations defended by the two authors are part of a non-hegemonic current within the Catholic Church. Attempting to contextualize more widely the dialogue between the movement in question and the History, we analyze the contributions of the Comissão de Estudos e História da Igreja na América Latina (CEHILA) for the historiography of religion in Brazil and also its contributions to think critically and self-criticism the history of Christianity in Latin America. Lastly we also discuss some reactions to the theologians of Liberation and its incorporation of historiography and marxism, by other segment theologians, of that Church. About significant group of those critics, we limit ourselves to analyze the criticisms of Liberation Theology through documents published by four of these defenders of Catholic Orthodoxy: Joseph Ratzinger, Friar Boaventura Kloppenburg, Urban Ziles and Karl Josef Romer. The intention is to identify the different conceptions of history and the conflicts of representation within the Catholic Church.